Enseñar a emprender en universidades de la Región de Coquimbo, Chile: Perfil docente y prácticas de enseñanza - Araya-Pizarro, Sebastián Cristóbal; Avilés-Pizarro, Nibaldo Bernardo (Universidad de Costa Rica, 2020)
Currently, the contribution of entrepreneurial education to business activity and the challenge of its effective teaching are widely documented. The following article describes the profile and practices of those who teach entrepreneurship in Chilean universities. The study, of mixed sequential methodological design, included interviews to 20 teachers who teach entrepreneurship subjects, along with the application of a survey to 329 students of 13 careers from 5 university campuses in Region of Coquimbo (Chile), during 2015. The results show that those who teach entrepreneurship have a homogenous profile in terms of personal, academic and professional characteristics. In addition, both students and teachers prefer teachers who undertake, to whom they attribute entrepreneurial, personal and didactic superior skills (teacherpreneur). It’s concluded that there is a high appreciation of the students regarding the activities, methods and entrepreneurship tools taught, which mostly coincide between institutions and university careers. However, the need to configure a more integral curriculum that enhances both cognitive and affective dimensions is observed, where the training delivered has a more practical nature and links with the business world (networking).